O serviço de atendimento educacional especializado (AEE): limites e possibilidades da proposta de educação inclusiva em escolas municipais de João Pessoa - PB - Moura, Yara Clécia Pereira (2017)
The present work has the objective of discussing and analyzing the proposal of inclusive education in Municipal Schools of the city of João Pessoa / PB and the nuances of the Specialized Educational Assistance Service to subsidize the educational context propagated by inclusive education. Reflecting on the contributions of this Service, as one of the largest special education services, implemented in Brazilian public schools, complementary to the education of students with special educational needs (SEN) in regular rooms. This reflection will be based on the experiences and perspectives of the teachers of the regular classroom and the teachers of the AEE room who work with these students in municipal schools of elementary school I of João Pessoa / PB. During our studies, we propose to outline the profile of teachers working in the schools surveyed, to understand how the qualification / training process offered by the State is offered to these teachers, as well as to reflect on the challenges, perspectives and possibilities for working with students with SEN and the implementation of this educational proposal. The methodological procedures used are of an exploratory nature, with a qualitative approach, using the technique of data collection in an intentional sample, applied through a semi-structured questionnaire as instrument of this research, carried out after approval by the Ethics Research Council, respecting ethical and secrecy of the subjects. The analysis of the collected data occurred in consonance with the bibliographical framework referenced in the course of this dissertative work. Guided by the historical-dialectical materialist approach, we seek to understand the current situation of Education Policy, which is inserted in a structural context, placing inclusive education policy within the broad context of economic, political and cultural restructuring. Based on the research carried out, it can be seen that the inclusion proposal does not fit the paradigm of the Living Education Policy, but rather requires profound modifications of this traditional / conservative educational policy. Regarding the incentive of federal entities with investments in Education Policy, with emphasis on the proposal of inclusive education, with direct repercussion on the valorization of teachers - continuing education policy, satisfactory salary costs, greater functionality in projects of accessibility, both structural, as well as pedagogical and curricular activities, investments in teaching materials and assisted technologies for working with students with special educational needs (SEN). Reaffirming with this, the functional organization of public schools, as a space that constitutes the means and purpose for the operationalization of the Brazilian Education Policy.